Effects of FGFR gene polymorphisms on response and toxicity of cyclophosphamide-epirubicin-docetaxel-based chemotherapy in breast cancer patients - Chen, Lu (BMC Cancer, 2018)
BACKGROUND: The chemotherapy resistance and toxicity of chemotherapy are major problems in breast cancer treatment. However, candidate biomarkers for predicting clinical outcomes and better prognosis remain lacking. METHODS: In this study, we analyzed possible impact of 8 genetic variants of fibroblast growth factor receptor1–4 (FGFR1–4) on the treatment response and toxicities in 211 breast cancer patients. DNA was extracted from peripheral blood cells, and the genotypes were examined using the TaqMan Pre-Designed SNP Genotyping Assays. RESULTS: The FGFR4 rs1966265 and FGFR2 rs2981578 contributed to clinical outcome of breast cancer treated with docetaxel–epirubicin-cyclophosphamide (CET)-based chemotherapy. For rs1966265, AA genotype had significant correlation with the clinical response to neoadjuvant chemotherapy (NCT) when compared with GG and AG/GG genotype (P = 0.019 and P = 0.004, respectively). Moreover, A allele of FGFR2 rs2981578 had significant rates of response (P = 0.025). In addition, rs2420946 CC genotype was associated with higher frequency of toxicities compared with TT and CT/TT genotypes (P = 0.038 and P = 0.019, respectively). Also, rs2981578 AG genotype showed higher frequency of toxicities compared with GG genotype (P < 0.0001). CONCLUSIONS: The results suggest these polymorphisms, especially rs1966265 and rs2981578, might be candidate pharmacogenomics factors to the response and prognosis prediction for individualized CET-based chemotherapy in breast cancer patients.